Systematic expression analysis of m6A RNA methyltransferases in clear cell renal cell carcinoma. Issue 6 (3rd May 2021) - Gundert, Larissa; Strick, Alexander; von Hagen, Felix; Schmidt, Doris; Klümper, Niklas; Tolkach, Yuri; Toma, Marieta; Kristiansen, Glen; Ritter, Manuel; Ellinger, Jörg
Abstract: Objectives: To investigate the regulation of the N‐6‐methyladenosine (m 6 A) methyltransferases METTL3, METTL14, WTAP, KIAA1429, and METTL4, referred to as "m 6 A writers, " in clear cell renal cell carcinoma (ccRCC), and other RCC subtypes in respect of the potential prognostic value. Patients and methods: Tissue samples were collected within the framework of the Biobank at the Center for Integrated Oncology Bonn. The expression of the methyltransferases was systematically determined in clear cell renal carcinoma (ccRCC) on the RNA (real‐time PCR) and protein level (immunohistochemistry). Additionally, protein expression of the m 6 A writers was further investigated in papillary RCC, chromophobe RCC, sarcomatoid RCC, oncocytoma, and normal renal tissue (immunohistochemistry). Results: The expression of all m 6 A‐methyltransferases was significantly downregulated in ccRCC compared to benign renal tissue. Low m 6 A‐methyltransferase levels were correlated with higher histological grade, advanced pT‐stage, pN‐stage, and metastatic disease. Reduced m 6 A‐methyltransferase expression was associated with shorter overall survival. Conclusion: In conclusion, m 6 A‐methyltransferases are dysregulated in ccRCC and might act as tumor suppressor genes, which could be of particular importance for future diagnostic and therapeutic options.